PERMAINAN TRADISIONAL DAN KONTRIBUSINYA UNTUK SIKAP HORMAT ANAK - Thomas Reno Pratama Hadi; Gregorius Ari Nugrahanta (Institut Pendidikan Tapanuli Selatan, 2021)
The purpose of this research was to develop a manual for traditional games to improve the character of respect for children aged 9-12 years. This research used the ADDIE Research and Development (R&D) method which involves seven teachers from various regions for needs analysis, seven validators for expert judgment, and six children for limited manual testing. The results show that 1) traditional game manuals to development the character of respect for children aged 9-12 years were developed based on the stages of the ADDIE type, namely Analyze, Design, Develop, Implement, and Evaluate; 2) The quality of the traditional game manual received a score of 3.81 (range 1-4) and was declared